Cardiometabolic Effects of Sus barbatus Meat Consumption: Analysis of Blood Cholesterol Levels and Cardiac Histopathological Alterations in Mus musculus - Kerapetse Sehularo; Joseph Mbogua; Kamatara Kanifa (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the effects of pork (Sus scrofa domesticus) and beef (Bos taurus) consumption on total cholesterol levels and the histopathological structure of the heart in male ICR mice (Mus musculus). Methodology: This study employed an experimental laboratory design using a Completely Randomized Design (CRD). Fifteen male ICR mice (Mus musculus), aged 2–3 months and weighing 25–30 g, were divided into control, pork-fed (Sus barbatus), and beef-fed (Bos taurus) groups. After 30 days of treatment, blood samples were analyzed for total cholesterol levels, and heart tissues were examined histologically using the Hematoxylin-Eosin (HE) staining method. Data were analyzed statistically using SPSS. Main Findings: Pork consumption increased total cholesterol in male ICR mice to 704 mg/dL. Beef-fed mice showed moderate cholesterol levels (319–321 mg/dL), while the control remained normal (114 mg/dL). Heart weight was highest in the pork group (0.25 g). Histopathology revealed fat cell accumulation only in pork-fed mice, with normal heart structures in both control and beef-fed groups. Novelty/Originality of this study: This study uniquely investigates the direct impact of pork consumption on total cholesterol levels and cardiac histopathology in male ICR mice. It provides new evidence of fat accumulation in heart tissue due to pork intake, contributing to early detection of dietary-induced cardiac risks and expanding current understanding of food-based cardiovascular effects in animal models.